Response of selected chemical properties of extremely acidic soils on the application of limes, rice husk biochar and zeolite - Gina Aliya Sopha; Catur Hermanto; Huub Kerckhoffs; Julian A Heyes; James Hanly (Brawijaya University, 2022)
Extremely acidic soils have low pH, high concentration of exchangeable Al3+ and low cation exchange capacity (CEC) that cause severe growth for most plants. The study was conducted in the soil laboratory of the Indonesian Vegetable Research Institute, Lembang, from June to August 2019. A randomised complete block design with seventeen treatments, three replications, and three incubation times (3, 30 and 60 days) was deployed to assess the effect of rates of soil amendments, namely 5 to 30 t liming materials ha-1, 5 to 20 t rice husk biochar ha-1, and 5 to 20 t zeolite ha-1 on extremely acidic soils. The results showed that lime materials, i.e., lime, agriculture limestone, and hydrated lime had a similar effect on increasing soil pH and reducing exchangeable Al3+. Calcium super seemed more effective in increasing soil pH and reducing exchangeable Al3+ than local lime due to the high CCE value. However, there was no significant response to the highest rice husk biochar and zeolite rate on soil pH and exchangeable Al3+. Rice husk biochar increased the concentration of K+ and zeolite raised the concentration of Na+. However, the effect was minimal. About 3 t lime ha-1 or 2.5 t calcium super ha-1 or equivalent to 1.5 to 2 times exchangeable Al3+ is required to obtain the soil pH target of 4.8, where the exchangeable Al3+ was less than 0.5 cmol(+) kg-1.